Deformation Process and Mechanism of the Frontal Megathrust at the Nankai Subduction Zone. (20th April 2022) - Kimura, Gaku; Hamada, Yohei; Yabe, Suguru; Yamaguchi, Asuka; Fukuchi, Rina; Kido, Yukari; Maeda, Lena; Toczko, Sean; Okuda, Hanaya; Ogawa, Nobuhiro; Morioka, Hitoshi; Ujiie, Kohtaro; et al.
Abstract: The frontal megathrust of the Nankai Trough subduction zone is recognized as a seismogenic fault based on a record of frictional heating, but the underlying micromechanical processes that act on the fault surface are poorly known. Here we present a layer of fault gouge ∼2 mm thick within a core drilled across the megathrust, in which smectite‐rich siltstone has been transformed into a preferentially oriented illite aggregate. The nearly complete breakdown of smectite is consistent with fast frictional heating on this fault; however, the microtextures of the gouge and its surroundings are asserted one produced experimentally by slow slip. We suggest that slow slip with small shear strain has overprinted the textures produced by the previous faster and larger slip. This interpretation based on microtectonic evidence suggests a slow slip around the frontal megathrust took place during slow down, afterslip, or interseismic as observed now going in subduction zone. We suggest that the illite‐dominated gouge is conditionally stable, likely to shift from rapid to slow slip at different times. Plain Language Summary: Recent dense seismic observations have revealed that both fast and slow earthquakes occur in the Nankai Trough megathrust, but the micro‐processes on the fault surface have not yet been clarified. In this study, we performed three‐dimensional structural analysis, electron microscopy observation, and microdomain X‐ray mineral analysis of the Nankai Trough frontal megathrust sample, which are presumed to be the earthquake generating fault. The results show that smectite is lost due to high velocity slip, and a composite planar fabric with relatively slow and small deformation is observed to override the fast deformation. Our observations suggest that the fault may experience both of fast and slow slip at different times. Key Points: Microscopic and mineral analysis were performed on the Nankai Trough frontal megathrust sample collected by drilling The development of the Y‐P‐R1 fabric was observed, along with traces of fast deformation accompanied by the disappearance of smectite Two types of deformations registered in the gouge suggest rapid to slow slip at different times on the same fault